5n-(9-5n)=9

Simple and best practice solution for 5n-(9-5n)=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-(9-5n)=9 equation:


Simplifying
5n + -1(9 + -5n) = 9
5n + (9 * -1 + -5n * -1) = 9
5n + (-9 + 5n) = 9

Reorder the terms:
-9 + 5n + 5n = 9

Combine like terms: 5n + 5n = 10n
-9 + 10n = 9

Solving
-9 + 10n = 9

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 10n = 9 + 9

Combine like terms: -9 + 9 = 0
0 + 10n = 9 + 9
10n = 9 + 9

Combine like terms: 9 + 9 = 18
10n = 18

Divide each side by '10'.
n = 1.8

Simplifying
n = 1.8

See similar equations:

| 2(x+3)=8(x-1) | | 21q+73=62q-51+8q | | B=(d/1-r) | | 8n+21n=-3 | | (25/8)(24/5) | | 3x-(x+1)=7 | | X+5+x+14=15 | | 3x+2y-5=ax+by+1 | | -144=-3-3(5+6k) | | 84x^2-238x-196=0 | | 7n+12=32 | | (25/8)(2/5) | | 24-x/3=6 | | 5(3x-5)=6(x-2)-19 | | (4n/7)+(3n/2)=-3 | | (12n+20)-4-8n=6-2n | | 3x^2+40x+112=0 | | 3/4x-1/4x=-11 | | 25/8*2/5 | | -13+5x=12 | | 1/(14-3x)=2/(5x+4) | | 0.7t=0.3+0.9t | | 2p+5r=a | | 3(5-2r)-2(-3r+1)= | | 10x-(4x-8)=50 | | 4(5-4k)=-60 | | 8-34= | | 4+6/x | | 14=5x+2 | | -3(x-8)=18 | | (6x+20)+(2x+4)=164 | | (3x+2)/4=16-2x |

Equations solver categories